Knowledge and Attitude of The Medical Staff Toward Poliomyelitis and Polio Vaccination Campaign: A Cross–Sectional Study in Al-Najaf Al -Ashraf City–Iraq - Hawraa Makki Kareem; Huda Ghazi Hameed (مجلة الكوفة الطبية)
Background: Medical staff needs to understand factors that affect poliomyelitis vaccination because their attitudes about vaccination are highly associated with rates of childhood vaccination if medical staff do not view a specific vaccine as necessary or acceptable, vaccination campaigns can be ineffective. Aim of the study: To assess the knowledge and attitudes of the medical staff toward poliomyelitis and polio vaccination campaigns. Patients and methods: A cross-sectional study conducted from 1st of January 2019 to 29th February 2020, and included (332) medical staff from randomly selected hospitals and primary health centers. Data were collected using a questionnaire designed for the study, which consists of three parts: socio-demographic and personal information, knowledge, and attitude. for knowledge, each correct answer scored 1 while the wrong one scored 0. For attitude, each “agree” answer scored 1 while “disagree” or “I don’t know” scored 0. Statistical analyses were done using SPSS version 26 and a P- value ≤0.05 was considered Statistically significant. Results: The study included 332 medical staff: 143 (43.1%) doctors, 77 (23.2%) dentists, and 112 (33.7%) pharmacists. The mean knowledge score was higher among doctors than dentists and pharmacists (18.22, 15.38, and 15.67, respectively, p = 0.0001). As age increased, the mean knowledge score also increased (20.22 for 50-59 years old vs. 14.81 for 23-29 years old, P = 0.0001). The attitude score followed the same trend, being higher among doctors and older age groups (2.97 vs. 2.68 and 2.82, P = 0.0001) and higher for the older age group (3 vs. 2.82, P = 0.0001).  Conclusions: The mean knowledge and attitude scores of doctors are significantly higher than dentists and pharmacists and for the older age group.